Strengthening Pedagogical Foundations in the Era of Digital Transformation - Purwinarti, Wiwin; Dwiyanti, Yanyan; Aris Munandar, Imam; Hidayat, Sholeh (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2025)
The rapid advancement of information technology in the era of digital transformation presents new challenges for the education sector, particularly in strengthening pedagogical foundations. This study aims to explore strategies for enhancing teachers' pedagogical competencies in response to educational demands in the digital age. A qualitative approach was employed, with data collected through observations, interviews, and document analysis involving teachers who have participated in competency enhancement programs. The findings indicate that strengthening teachers' pedagogical competencies focuses not only on the use of technology in learning but also on developing students' critical and creative thinking skills. Teachers play the role of facilitators who encourage active student participation and create collaborative learning environments through the utilization of digital learning resources. Furthermore, the study found that integrating technology into the curriculum and instruction can enhance student motivation and engagement, making learning more interactive and relevant to contemporary needs. The implications of this research highlight the importance for teachers to continuously develop their pedagogical competencies to adapt to ongoing changes and meet the expectations of 21st-century education.